Design of pure silica-based photonic crystal fiber for supporting 114 OAM modes transmission. (12th August 2021) - Liu, Qiang; Tai, Shengnan; Lu, Wenshu; Sun, Jiudi; Lv, Tingting; Liu, Chao; Sun, Yudan; Lv, Jingwei; Liu, Wei; Sun, Tao; Chu, Paul K
Abstract: A novel photonic crystal fiber (PCF) based on pure silica is designed to transmit 114 orbital angular momentum (OAM) modes in the wavelength range of 1.2 μ m–1.8 μ m. The PCF composed of a central round air-hole, ring-shaped core, and air-hole array ensures effective refractive index differences of the constituent vector modes above 10 −4 and stable transmission of the OAM modes. The finite element method is implemented to analyze the PCF. The confinement losses and nonlinear coefficients of all the eigenmodes at 1550 nm are less than 3.03 × 10 −7 dB m −1 and 1.30 w −1 km −1, respectively. In addition, the PCF shows higher effective refractive index difference, lower confinement loss, and nonlinear coefficient thus holding large promise in high-performance fiber communication systems.